Проблемні питання інформаційної безпеки у фармації - Ткаченко, Наталя Олександрівна; Мисюра, С. С. (My University, 2024)
У роботі за допомогою контент-аналізу було визначено основні проблеми інформаційно-безпекового середовища процесу надання фармацевтичної допомоги. На підставі експертного оцінювання фармацевтами науковцями та практиками визначили якість медико-фармацевтичної інформації, яку отримують споживачі ліків з різних джерел. In this work, using content analysis, the main problems of the information-safe environment of the process of providing pharmaceutical care were identified. Based on the expert assessment by pharmacists (scientists and practitioners), the quality of medical and pharmaceutical information received by consumers of drugs from various sources was determined.
Keywords: фармацевтична інформація; інформаційна безпека; безпека пацієнтів; pharmaceutical information; information safety; patient safety